The multiliteracies classroom - Mills, Kathy, 1974- (New perspectives on language and education., 2011)
The multiliteracies approach to literacy education has become established as an accessible and effective paradigm for classroom practice in the 21st century. The Multiliteracies Classroom enlivens this theory with its vivid description of events in a real classroom. Teachers will identify with the lively transcripts of classroom interactions, and be inspired to widen students' access to new literacy practices in an increasingly digital and globalised world. The possibilities and constraints that can be encountered when implementing multiliteracies are explored in detail. Educators know from ex.